The Role of Foreign Investor in the Effect of Market Sentiment on Post-Earnings Announcement Drift: Evidence from Korean Stock Market - Shin, Hee Jeong(신희정) (신산업경영저널, 2021)
This study investigates whether the magnitude of post-earnings announcement drift (hereafter, PEAD) attributed to market sentiment differs in foreign investor ownership of firms. Given that PEAD as an accounting-based market anomaly occurs due to investor’s cognitive bias (i.e., inertia) which is focused on market sentiment trend, it is conjectured that PEAD would be lower in firms devoted by sophisticated investors. Considering foreign investor ownership as a proxy for the measure of investor sophistication, this study shows that the magnitude of market sentiment - related PEAD decreases in foreign investor ownership, in general. However, this result is effective only for period with upwardly-shifted market sentiment. Taken together, the findings suggest that foreign investors play a role in improvements of capital market’s efficiency and especially make an explicit function as investors not being blinded when investors’ inertia arises under upwardly-shifted market sentiment. This study offers significant implication in academic and practice field in extending literature on a determinant of PEAD as one of the market anomalies and in helping market participants understand emerging market increasing proportion of foreign investors and develop an investment strategy. KCI Citation Count: 0